Reforming Vocational Didactics by Implementing a New VET Teacher Education in Denmark: Tensions and Challenges Reflected in Interviews with Vocational College Teachers - Duch, Henriette; Andreasen, Karen E. (International Journal for Research in Vocational Education and Training, 2015)
A new education program, Diploma of Vocational Pedagogy, has recently been implemented in Denmark to upskill vocational college teachers and improve didactics at VET colleges in general. Among many challenges, vocational college teachers have to adapt their pedagogy to a large number of students from backgrounds with no tradition for education. Despite historical changes, the education as vocational college teacher also struggles with the interplay between theory and practice in the program and great diversity among vocational college teachers. Based on empirical data from focus group interviews with students from the Diploma of Vocational Pedagogy program and concepts developed by Bernstein and Bourdieu, the article analyzes how these aspects might affect the development of new vocational didactics. We know that it is not easy to change the culture of educational institutions, and the analysis uncovers several factors that are expected to hamper the development processes.